A copper-manganese composite oxide catalyst, a preparation method and application thereof

CN122875244APending Publication Date: 2026-10-09HEBEI AGRICULTURAL UNIV.
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611167814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种铜锰复合氧化物催化剂、其制备方法及应用,以解决现有竹醋液制备过程中焦油生成和脱除困难、后处理流程复杂、催化剂与竹质废料热解体系适配性不足等问题

Benefits of technology

[0025](1)本发明采用溶胶凝胶法结合惰性气氛煅烧和空气焙烧制备铜锰复合氧化物催化剂,制备温度较低,工艺简单,原料易得,不需要水洗,变量易控,适合大量制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a copper-manganese composite oxide catalyst, a preparation method and application thereof, and belongs to the technical field of nanometer materials and catalytic conversion of bamboo tar. The copper-manganese composite oxide catalyst is prepared by adopting a sol-gel method combined with inert atmosphere calcination and air calcination, the prepared copper-manganese composite oxide catalyst provides a multi-valence state redox cycle through Mn-based oxides, Cu doping controls the crystal lattice structure, the surface electronic structure and the oxygen vacancy distribution, so that the copper-manganese composite oxide catalyst is suitable for the adsorption, activation and oxidative cracking of heavy components in bamboo tar. The copper-manganese composite oxide catalyst can be applied to the preparation of low-tar bamboo vinegar liquid through photodriven pyrolysis of bamboo waste, the bamboo waste is placed in a photothermal tube reactor, the catalyst is placed in a catalytic area through which pyrolysis gas flows, the volatile components generated by the pyrolysis of the bamboo waste are fully contacted with the catalyst when leaving the pyrolysis area, so that the in-situ catalytic conversion of tar components is promoted and the low-tar bamboo vinegar liquid is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of nanomaterials and catalysis, specifically to a copper-manganese composite oxide catalyst, its preparation method, and its application. Background Technology

[0002] Bamboo processing generates a large amount of bamboo waste, including bamboo powder, bamboo shavings, and scraps. Pyrolysis technology can convert this bamboo waste into bamboo charcoal, combustible gases, and liquid products. The liquid products, after condensation, separation, and purification, yield bamboo vinegar. Bamboo vinegar contains organic acids, phenols, aldehydes, ketones, alcohols, and heterocyclic compounds, and has applications in ecological agriculture, antibacterial preservation, and daily chemical industries.

[0003] In the process of preparing bamboo vinegar from bamboo waste through pyrolysis, components such as hemicellulose, cellulose, and lignin undergo reactions such as cracking, dehydration, decarboxylation, condensation, and secondary polymerization, which easily produce bamboo tar containing phenols, aromatics, and large oxygen-containing molecules. Bamboo tar is characterized by its viscosity, difficulty in separation, dark color, and negative impact on the quality of bamboo vinegar. Conventional processes usually require post-treatment steps such as settling and aging, filtration, distillation, or adsorption to remove the tar, which results in problems such as long cycle time, cumbersome process, high equipment cost, and loss of effective components.

[0004] Catalytic cracking or catalytic reforming are important technical approaches for tar removal. Developing a catalyst that is suitable for bamboo waste pyrolysis systems, easy to prepare, and structurally stable is of great significance for the efficient preparation of low-tar bamboo vinegar. Summary of the Invention

[0005] The purpose of this invention is to provide a copper-manganese composite oxide catalyst, its preparation method and application, to solve the problems of difficulty in tar generation and removal, complex post-processing, and insufficient compatibility between the catalyst and the bamboo waste pyrolysis system in the existing bamboo vinegar preparation process.

[0006] This invention is implemented as follows:

[0007] The copper-manganese composite oxide catalyst provided by this invention is a manganese-based composite oxide containing Cu, Mn, and O, wherein the molar ratio of Cu to Mn is 0.1:1 to 0.5:1, preferably 0.1:1. The preferred catalyst is denoted as Cu. 0.1 Mn1O x After normalization based on the total number of metal cations in spinel-type manganese oxides being 3, it can be expressed as (Cu 0.27 Mn 2.73 ) 1-δ O4, where δ represents an oxygen vacancy or non-stoichiometric oxygen defect.

[0008] The preparation method of the copper-manganese composite oxide catalyst provided by the present invention includes the following steps:

[0009] a. Dissolve citric acid, copper nitrate, and manganese nitrate in deionized water and stir until homogeneous to form a mixed solution;

[0010] b. Add nitric acid and ethylenediamine to the mixed solution obtained in step a, continue stirring, and then add ammonia dropwise to adjust the pH to 6-7;

[0011] c. Heat and stir the solution obtained in step b until a gel-like sample is formed; dry and age the gel-like sample to obtain the catalyst precursor.

[0012] d. Calcine the catalyst precursor obtained in step c under an inert atmosphere;

[0013] e. The sample obtained in step d is calcined in air and then cooled to obtain a copper-manganese composite oxide catalyst.

[0014] Preferably, step d specifically involves: transferring the catalyst precursor obtained in step c into a quartz tube, introducing an inert atmosphere to remove air, then heating it to 400°C at a heating rate of 10°C / min, calcining it for 4 h, and then allowing it to cool naturally after calcination.

[0015] Preferably, step e specifically involves: transferring the sample obtained in step d into a muffle furnace, heating it to 400°C at a heating rate of 10°C / min in an air atmosphere, holding it at that temperature for 4 hours, and then allowing it to cool naturally.

[0016] Preferably, the drying and aging conditions in step c are: drying and aging at 80°C for 24 hours.

[0017] This invention utilizes copper nitrate and manganese nitrate as metal precursors and citric acid as a complexing agent to prepare a copper-manganese composite oxide catalyst via sol-gelation, drying and aging, inert atmosphere calcination, and air roasting. This catalyst can be used for in-situ conversion of bamboo tar in the pyrolysis of bamboo waste or photo-driven thermocatalytic preparation of bamboo vinegar, promoting the oxidative cracking and reforming of phenols, aromatics, and oxygen-containing heavy components in the pyrolysis gas, thereby reducing tar residue in the bamboo vinegar and improving its quality. The preparation method of this invention is simple, the conditions are mild, the raw materials are readily available, and water washing is not required. It is suitable for use in conjunction with continuous production processes and equipment for the pyrolysis of bamboo waste to prepare low-tar bamboo vinegar.

[0018] Specifically, the light-driven pyrolysis is carried out in a photothermal tube reactor. The bamboo waste is placed in the photothermal tube reactor, and the copper-manganese composite oxide catalyst is placed in the catalytic zone through which the pyrolysis gas flows. The bamboo waste undergoes pyrolysis under light irradiation. The volatile components produced by pyrolysis come into full contact with the catalyst when leaving the pyrolysis zone, thereby promoting the in-situ catalytic conversion of tar components before condensation and obtaining low-tar bamboo vinegar.

[0019] Preferably, the reaction atmosphere in the light-driven pyrolysis process is air.

[0020] Preferably, the air flow rate is 20-60 mL / min, more preferably 40 mL / min.

[0021] Preferably, the light intensity is 0.4-1.8 kW·m -2 More preferably 1.2 kW·m -2 .

[0022] Preferably, the mass ratio of catalyst to bamboo waste is 3%-30%, more preferably 10%.

[0023] Preferably, the bamboo waste is bamboo powder, bamboo shavings, bamboo processing residues, or a mixture thereof.

[0024] The present invention has the following beneficial effects:

[0025] (1) The present invention uses the sol-gel method combined with inert atmosphere calcination and air roasting to prepare copper-manganese composite oxide catalyst. The preparation temperature is low, the process is simple, the raw materials are readily available, no water washing is required, the variables are easy to control, and it is suitable for large-scale preparation.

[0026] (2) In the catalyst of the present invention, Mn-based oxide provides multi-valence redox cycle, Cu doping regulates lattice structure, surface electronic structure and oxygen vacancy distribution, and the synergistic effect between copper element and manganese oxide regulates the lattice structure, metal valence state and surface active oxygen migration ability of the catalyst, making it suitable for the adsorption, activation and oxidative cracking of heavy components in bamboo tar.

[0027] (3) The catalyst of the present invention has a loose and porous aggregated morphology, which is beneficial to the mass transfer of pyrolysis gas and the exposure of active sites.

[0028] (4) The catalyst of the present invention is applied to the in-situ conversion of bamboo tar in the process of preparing bamboo vinegar by photo-driven pyrolysis of bamboo waste. It can be used in conjunction with bamboo waste pyrolysis and photo-driven thermocatalysis device, which can reduce the tar residue entering the condensate and simplify the preparation process of low tar bamboo vinegar. Attached Figure Description

[0029] Figure 1 This is a flowchart illustrating the preparation process of the copper-manganese composite oxide catalyst of this invention.

[0030] Figure 2 It is the (Cu) obtained in Example 1 0.27 Mn 2.73 ) 1-δ XRD pattern of O4 catalyst.

[0031] Figure 3 It is the (Cu) obtained in Example 1 0.27 Mn 2.73 ) 1-δScanning electron microscope image of the O4 catalyst.

[0032] Figure 4 It is the (Cu) obtained in Example 1 0.27 Mn 2.73 ) 1-δ BET and transmission electron microscopy characterization of O4 catalyst.

[0033] Figure 5 It is the (Cu) obtained in Example 1 0.27 Mn 2.73 ) 1-δ Elemental distribution diagram of O4 catalyst.

[0034] Figure 6 It is the (Cu) obtained in Example 1 0.27 Mn 2.73 ) 1-δ XPS spectra of O4 catalyst.

[0035] Figure 7 It is in Example 1 (Cu 0.27 Mn 2.73 ) 1-δ O4 catalyst at 1.2 kW·m -2 The graph shows the changes in bamboo vinegar yield and tar yield over time during photo-driven thermocatalytic preparation of bamboo vinegar under light intensity. Detailed Implementation

[0036] The present invention is further described below through specific embodiments, but these embodiments do not constitute a limitation on the scope of protection of the present invention. Unless otherwise specified, the embodiments employ a light-driven pyrolysis device, and the bamboo waste is dried bamboo powder. The bamboo waste and catalyst are loaded into a quartz tube, and the quartz tube is placed in a photothermal tube reactor. The volatile products generated by pyrolysis are collected by a condensation system to obtain bamboo vinegar. The yield of bamboo vinegar is calculated according to the ratio of the mass of bamboo vinegar to the mass of bamboo powder; the tar yield is calculated by weighing the tar after drying the bamboo vinegar in an 80 ℃ oven, and then using the ratio of the tar mass to the mass of bamboo vinegar.

[0037] Example 1 Cu 0.1 Mn1O x Preparation of copper-manganese composite oxide catalysts and their application in photo-driven pyrolysis

[0038] Combination Figure 1At room temperature, weigh 2.5 g of citric acid, 0.096 g of Cu(NO3)2·3H2O and 1.0 g of Mn(NO3)2·4H2O and place them in a beaker. Add 20 mL of deionized water and dissolve them completely under magnetic stirring to form a homogeneous mixed solution. Then add 1.2 mL of nitric acid and 0.6 mL of anhydrous ethylenediamine in sequence and continue stirring. After the solution stabilizes, add ammonia water dropwise to adjust the pH of the system to 6-7.

[0039] The above solution was heated to 80 °C and stirred continuously until it gradually dried to form a gel-like sample. The gel-like sample was placed in a forced-air drying oven and aged at 80 °C for 24 h to obtain the catalyst precursor. The catalyst precursor was transferred to a quartz tube, and argon gas was introduced for 40 min to purge air. Then, the temperature was increased to 400 °C at a rate of 10 °C / min and calcined under an argon atmosphere for 4 h. After calcination, it was allowed to cool naturally under an argon atmosphere. Subsequently, it was transferred to a muffle furnace and heated to 400 °C at a rate of 10 °C / min under an air atmosphere and held for 4 h to remove residual carbon and form a stable copper-manganese composite oxide structure. After natural cooling, Cu was obtained. 0.1 Mn1O x Catalyst. This catalyst, after normalization to the total number of spinel-type manganese oxide cations, can be denoted as (Cu... 0.27 Mn 2.73 ) 1-δ O4.

[0040] The Cu obtained in this embodiment 0.1 Mn1O x The application of catalysts in light-driven pyrolysis is as follows: 5.0g of dry bamboo powder and Cu... 0.1 Mn1O x 0.5 g of catalyst was loaded into a quartz tube, which was then placed inside a photothermal tube reactor. Air was introduced at a flow rate of 40 mL / min at a power output of 1.2 kW·m⁻¹. -2 The bamboo vinegar solution was collected by condensation after undergoing a light-driven pyrolysis catalytic reaction under illumination.

[0041] Cu prepared in Example 1 0.1 Mn1O x The catalyst was characterized by XRD, SEM, BET, TEM, elemental distribution analysis, and XPS. The results are as follows: Figures 2-6 As shown.

[0042] XRD patterns as follows Figure 2 As shown. The XRD pattern shows Cu 0.1 Mn1O xThe main diffraction peaks of the catalyst are similar to those of the Mn3O4 standard card, indicating that the catalyst is mainly composed of manganese oxide spinel structure. At the same time, no obvious strong CuO diffraction peaks were observed, indicating that Cu element has a high degree of dispersion in Mn oxide matrix.

[0043] SEM results are as follows Figure 3 As shown in the SEM image, the catalyst exhibits a loose, porous, granular aggregate structure with numerous gaps and open channels between the particles. This structure facilitates the passage of pyrolysis gases from bamboo waste through the catalyst bed and increases the contact probability between heavy tar components and catalytically active sites.

[0044] BET and TEM characterization, such as Figure 4 As shown. The nitrogen adsorption-desorption curves indicate that the sample has mesoporous structure characteristics, Cu 0.1 Mn1O x The catalyst has a specific surface area of ​​approximately 36.04 m². 2 / g. This type of mesoporous and slit-type pore structure can provide mass transfer channels for the adsorption, diffusion and catalytic cracking of tar molecules. Clear lattice fringes can be observed in the TEM image, where the lattice spacing of about 0.210 nm corresponds to the CuMn2O4 (400) crystal plane and the lattice spacing of about 0.258 nm corresponds to the Mn3O4 (211) crystal plane.

[0045] Element distribution map as follows Figure 5 As shown, O, Mn and Cu elements are uniformly distributed in the catalyst plate region, with no obvious elemental segregation or large-size agglomeration, indicating that the sol-gel process is conducive to the uniform recombination of Cu and Mn components in the precursor and the formation of a uniform structure.

[0046] XPS diagrams, such as Figure 6 As shown. In the Cu 2p spectrum, Cu mainly exists as Cu. 2+ The form exists and remains relatively stable; Mn exists in the Mn 2p spectrum. 2+ Mn 3+ and Mn 4+ Multivalent species, including Mn species, can form redox cycles. Together with Cu-Mn-O interfaces and surface active oxygen species, they promote the adsorption, activation, and decomposition of phenols, aromatics, and oxygen-containing heavy components in bamboo tar.

[0047] Based on the combined results of XRD, SEM, TEM, BET, elemental distribution, and XPS, the Cu obtained in this embodiment is... 0.1 Mn1O x The catalyst has a stable copper-manganese composite oxide structure, uniform elemental distribution, mesoporous mass transfer channels, and surface active oxygen species that can participate in redox cycles.

[0048] Examples 2-9: Effects of different photo-driven thermocatalytic intensities on the yields of bamboo vinegar and tar

[0049] This set of examples illustrates the effect of light-driven heat input conditions on the yield of bamboo vinegar and tar. Except for the difference in light intensity, all other conditions are the same in this set of examples: bamboo powder dosage is 5.0 g, Cu... 0.1 Mn1O x The amount of catalyst (the catalyst obtained in Example 1) was 0.50 g. The bamboo powder and the catalyst were loaded together into a quartz tube and placed in a photothermal tube reaction apparatus. The air flow rate was 40 mL / min. The reaction products were collected by a condensation system.

[0050] In Example 2, the light intensity was set to 0.4 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 19.2% and a tar yield of 0.31%.

[0051] In Example 3, the light intensity was set to 0.6 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 30.2% and a tar yield of 0.86%.

[0052] In Example 4, the light intensity was set to 0.8 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 25.4% and a tar yield of 1.02%.

[0053] In Example 5, the light intensity was set to 1.0 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 25.6% and a tar yield of 1.24%.

[0054] In Example 6, the light intensity was set to 1.2 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 37.8% and a tar yield of 1.24%.

[0055] In Example 7, the light intensity was set to 1.5 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 36.8% and a tar yield of 4.24%.

[0056] In Example 8, the light intensity was set to 1.8 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 35.8% and a tar yield of 5.23%.

[0057] In Example 9, the light intensity was set to 2.1 kW·m. -2 The remaining conditions were the same as those in this group; the bamboo vinegar was collected by condensation after the reaction, with a bamboo vinegar yield of 25.6% and a tar yield of 16.04%.

[0058] Table 1. Comparison of bamboo vinegar and tar yields under different light intensities.

[0059]

[0060] Table 1 shows that as light intensity increases, the degree of bamboo powder pyrolysis intensifies, and the yield of bamboo vinegar initially increases and then decreases. The light intensity was 1.2 kW·m². -2 At that time, the yield of bamboo vinegar reached 37.8%, and the yield of tar was 1.24%; the light intensity was increased to 2.1 kW·m -2 At that point, the tar yield rose to 16.04%, indicating that excessively high heat input easily leads to the formation of heavy tar or intensified secondary condensation. Therefore, a light intensity of 1.2 kW·m is preferred. -2 .

[0061] Examples 10-13: Effects of different atmospheres and control catalysts on the preparation of bamboo vinegar from bamboo waste by pyrolysis

[0062] This set of examples illustrates the effects of reaction atmosphere and oxide catalyst on the quality of bamboo vinegar. Except for the atmosphere and catalyst, all other conditions were the same: bamboo powder dosage 5.0 g, particle size 20 mesh, catalyst to bamboo powder mass ratio 10%, and atmosphere flow rate 40 mL / min.

[0063] In Example 10, the reaction atmosphere was N2, no catalyst was added, the bamboo powder particle size was 20 mesh, and the atmosphere flow rate was 40 mL / min; the resulting bamboo vinegar solution had a pH of 3.41 and a density of 1.025 g / cm³. 3 The relative content of organic acids was 23.0%, the yield of bamboo vinegar was 35.3%, and the yield of tar was 8.41%.

[0064] In Example 11, the reaction atmosphere was N2, the catalyst was potassium permanganate, the bamboo powder particle size was 20 mesh, and the atmosphere flow rate was 40 mL / min; the resulting bamboo vinegar solution had a pH of 3.52 and a density of 1.026 g / cm³. 3 The relative content of organic acids was 22.8%, the yield of bamboo vinegar was 35.1%, and the yield of tar was 8.43%.

[0065] In Example 12, the reaction atmosphere was air, no catalyst was added, the bamboo powder particle size was 20 mesh, and the atmosphere flow rate was 40 mL / min; the resulting bamboo vinegar solution had a pH of 3.39 and a density of 1.025 g / cm³. 3The relative content of organic acids was 22.6%, the yield of bamboo vinegar was 36.5%, and the yield of tar was 8.23%.

[0066] In Example 13, the reaction atmosphere was air, the catalyst was potassium permanganate, the bamboo powder particle size was 20 mesh, and the atmosphere flow rate was 40 mL / min; the resulting bamboo vinegar solution had a pH of 3.28 and a density of 1.017 g / cm³. 3 The relative content of organic acids was 27.8%, the yield of bamboo vinegar was 45.6%, and the yield of tar was 4.51%.

[0067] Table 2. Performance of bamboo vinegar under different atmospheres and control catalyst conditions

[0068]

[0069] Table 2 shows that under nitrogen atmosphere, the tar yield was above 8% under both catalyst-free and potassium permanganate conditions, indicating that a simple inert atmosphere is not conducive to tar oxidative cracking. After adding potassium permanganate under air atmosphere, the tar yield decreased from 8.23% to 4.51%, while the relative content of organic acids increased to 27.8%, indicating that an air atmosphere is beneficial for the conversion of tar components and the enrichment of organic acids.

[0070] Examples 14-17: Effects of different atmosphere flow rates on the preparation of bamboo vinegar from bamboo waste by pyrolysis

[0071] This set of examples illustrates the effect of atmosphere flow rate on the yield of bamboo vinegar, tar yield, and relative content of organic acids in a photo-driven pyrolysis-catalytic reaction. Except for the atmosphere flow rate, all other conditions were the same: bamboo powder dosage 5.0 g, particle size 20 mesh, air atmosphere, potassium permanganate catalyst, and catalyst-to-bamboo powder mass ratio 10%.

[0072] In Example 14, the air flow rate was set to 20 mL / min, and the other conditions were the same as those in this group; the resulting bamboo vinegar solution had a pH of 3.26 and a density of 1.017 g / cm³. 3 The relative content of organic acids was 27.9%, the yield of bamboo vinegar was 45.5%, and the yield of tar was 4.50%.

[0073] In Example 15, the air flow rate was set to 40 mL / min, and the other conditions were the same as those in this group; the resulting bamboo vinegar solution had a pH of 3.28 and a density of 1.017 g / cm³. 3 The relative content of organic acids was 27.8%, the yield of bamboo vinegar was 45.8%, and the yield of tar was 4.49%.

[0074] In Example 16, the air flow rate was set to 60 mL / min, and the other conditions were the same as those in this group; the resulting bamboo vinegar solution had a pH of 3.29 and a density of 1.018 g / cm³. 3The relative content of organic acids was 27.2%, the yield of bamboo vinegar was 45.3%, and the yield of tar was 4.59%.

[0075] In Example 17, the air flow rate was set to 120 mL / min, and the other conditions were the same as those in this group; the resulting bamboo vinegar solution had a pH of 3.43 and a density of 1.023 g / cm³. 3 The relative content of organic acids was 25.3%, the yield of bamboo vinegar was 42.3%, and the yield of tar was 4.87%.

[0076] Table 3. Performance of bamboo vinegar under different atmosphere flow rates

[0077]

[0078] Table 3 shows that when the air flow rate is 20-60 mL / min, the bamboo vinegar yield remains around 45%, and the tar yield remains around 4.5%. When the flow rate increases to 120 mL / min, the bamboo vinegar yield decreases to 42.3%, and the tar yield increases to 4.87%, indicating that excessively high flow rates shorten the contact time between volatile components and the catalyst, which is not conducive to the complete conversion of tar. Considering both the bamboo vinegar yield and the tar yield, the preferred air flow rate is 20-60 mL / min, and more preferably 40 mL / min.

[0079] Examples 18-22: Application Effects of Mn-based Composite Oxide Catalysts Modified by Different Metals

[0080] This set of examples compares the effects of different metal-modified Mn-based composite oxide catalysts on the quality of bamboo vinegar. Except for the type of catalyst, all other conditions were the same: bamboo powder dosage 5.0 g, particle size 20 mesh, air flow rate 40 mL / min, and catalyst to bamboo waste mass ratio 10%.

[0081] The preparation methods of the Mn-based composite oxide catalysts in Examples 18, 19, and 21 can refer to Example 1, maintaining the atomic ratio of metal to Mn elements at 1:10. For example, in the preparation of Ni... 0.1 Mn1O x In this case, simply replace Cu(NO3)2·3H2O in Example 1 with 0.116 g Ni(NO3)2·6H2O. In Example 22, MnO... x Preparation method of composite oxides and Cu 0.1 Mn1O x They are the same, except that copper nitrate is not added.

[0082] In Example 18, the catalyst was a Ni-Mn composite oxide, denoted as Ni. 0.1 Mn1O xAfter the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.14 and a density of 1.019 g / cm³. 3 The relative content of organic acids was 25.6%, the yield of bamboo vinegar was 33.5%, and the yield of tar was 4.48%.

[0083] In Example 19, the catalyst was a Ce-Mn composite oxide, denoted as Ce. 0.1 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.24 and a density of 1.021 g / cm³. 3 The relative content of organic acids was 24.8%, the yield of bamboo vinegar was 32.6%, and the yield of tar was 5.60%.

[0084] In Example 20, the catalyst was a Cu-Mn composite oxide, denoted as Cu. 0.1 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.12 and a density of 1.018 g / cm³. 3 The relative content of organic acids was 25.7%, the yield of bamboo vinegar was 31.2%, and the yield of tar was 1.42%.

[0085] In Example 21, the catalyst was a Co-Mn composite oxide, denoted as Co. 0.1 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.34 and a density of 1.024 g / cm³. 3 The relative content of organic acids was 23.7%, the yield of bamboo vinegar was 31.2%, and the yield of tar was 7.91%.

[0086] In Example 22, the catalyst was MnO. x Composite oxide, denoted as MnO x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.26 and a density of 1.022 g / cm³. 3 The relative content of organic acids was 24.6%, the yield of bamboo vinegar was 33.6%, and the yield of tar was 7.41%.

[0087] Table 4. Application effects of different metal-modified Mn-based composite oxide catalysts

[0088]

[0089] As shown in Table 4, Cu 0.1 Mn1O x The catalyst corresponding to the bamboo vinegar solution had the highest organic acid content (25.7%) and the lowest tar yield (1.42%). While Ni-Mn and Ce-Mn catalysts could reduce tar content to some extent, their tar yields were still lower than those of Cu catalysts.0.1 Mn1O x MnO x The high tar yield of the Co-Mn catalyst indicates that the synergistic effect between Cu and Mn is more suitable for in-situ conversion of bamboo tar and upgrading of bamboo vinegar.

[0090] Examples 23-27: Application Effects of Catalysts with Different Cu / Mn Molar Ratios

[0091] This set of examples illustrates the effect of the Cu / Mn molar ratio on the application performance of copper-manganese composite oxide catalysts. Except for the Cu / Mn molar ratio, all other conditions were the same: bamboo powder dosage 5.0 g, particle size 20 mesh, air flow rate 40 mL / min, and catalyst to bamboo waste mass ratio 10%.

[0092] The catalyst samples in this set of examples were prepared in accordance with Example 1. By adjusting the amount of Cu(NO3)2·3H2O added, copper-manganese composite oxide catalysts with different Cu / Mn molar ratios were prepared. The Cu / Mn molar ratios of each sample were 0.1:1, 0.2:1, 0.3:1, 0.4:1, and 0.5:1, respectively.

[0093] In Example 23, the Cu / Mn molar ratio of the catalyst sample was 0.1:1, denoted as Cu. 0.1 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 2.95 and a density of 1.013 g / cm³. 3 The relative content of organic acids was 28.8%, the yield of bamboo vinegar was 31.2%, and the yield of tar was 1.32%.

[0094] In Example 24, the catalyst sample had a Cu / Mn molar ratio of 0.2:1, denoted as Cu. 0.2 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.01 and a density of 1.013 g / cm³. 3 The relative content of organic acids was 27.6%, the yield of bamboo vinegar was 31.5%, and the yield of tar was 3.74%.

[0095] In Example 25, the catalyst sample had a Cu / Mn molar ratio of 0.3:1, denoted as Cu. 0.3 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.08 and a density of 1.015 g / cm³. 3 The relative content of organic acids was 26.4%, the yield of bamboo vinegar was 31.6%, and the yield of tar was 3.99%.

[0096] In Example 26, the catalyst sample had a Cu / Mn molar ratio of 0.4:1, denoted as Cu. 0.4 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.12 and a density of 1.018 g / cm³. 3 The relative content of organic acids was 25.7%, the yield of bamboo vinegar was 31.2%, and the yield of tar was 4.29%.

[0097] In Example 27, the catalyst sample had a Cu / Mn molar ratio of 0.5:1, denoted as Cu. 0.5 Mn1O x After the light-driven pyrolysis-catalytic reaction, the resulting bamboo vinegar solution had a pH of 3.32 and a density of 1.020 g / cm³. 3 The relative content of organic acids was 21.7%, the yield of bamboo vinegar was 31.0%, and the yield of tar was 4.38%.

[0098] Table 5. Application effects of catalysts with different Cu / Mn molar ratios

[0099]

[0100] Table 5 shows that the highest relative content of organic acids and the lowest tar yield were observed when the Cu / Mn molar ratio was 0.1:1. As the Cu / Mn molar ratio continued to increase, the relative content of organic acids gradually decreased, while the tar yield slightly increased. This indicates that the introduction of excessive Cu may alter the main structure of manganese oxides and the distribution of oxygen species on the surface, which is detrimental to bamboo tar conversion and organic acid enrichment. Therefore, a Cu / Mn molar ratio of 0.1:1 is preferred.

[0101] Examples 28-32: Application effects of different catalyst-to-material mass ratios

[0102] This set of examples is used to illustrate Cu in Example 1. 0.1 Mn1O x The effect of catalyst dosage on the preparation of low-tar bamboo vinegar was investigated. Except for the different mass ratio of catalyst to bamboo waste, all other conditions were the same: bamboo powder dosage 5.0 g, particle size 20 mesh, air flow rate 40 mL / min, and the catalyst used was Cu from Example 1. 0.1 Mn1O x .

[0103] In Example 28, the mass ratio of catalyst to bamboo waste was 3%; when the amount of bamboo powder used was 5.0 g, the amount of catalyst used was 0.15 g. The resulting bamboo vinegar solution had a pH of 2.95 and a density of 1.013 g / cm³. 3 The relative content of organic acids was 28.8%, the yield of bamboo vinegar was 31.2%, and the yield of tar was 3.69%.

[0104] In Example 29, the mass ratio of catalyst to bamboo waste was 5%; when the amount of bamboo powder used was 5.0 g, the amount of catalyst used was 0.25 g. The resulting bamboo vinegar solution had a pH of 2.93 and a density of 1.012 g / cm³. 3 The relative content of organic acids was 32.7%, the yield of bamboo vinegar was 31.3%, and the yield of tar was 3.24%.

[0105] In Example 30, the mass ratio of catalyst to bamboo waste was 10%; when the amount of bamboo powder used was 5.0 g, the amount of catalyst used was 0.50 g. The resulting bamboo vinegar solution had a pH of 2.84 and a density of 1.009 g / cm³. 3 The relative content of organic acids was 36.8%, the yield of bamboo vinegar was 31.5%, and the yield of tar was 1.31%.

[0106] In Example 31, the mass ratio of catalyst to bamboo waste was 20%; when the amount of bamboo powder used was 5.0 g, the amount of catalyst used was 1.00 g. The resulting bamboo vinegar solution had a pH of 2.72 and a density of 1.008 g / cm³. 3 The relative content of organic acids was 37.1%, the yield of bamboo vinegar was 32.4%, and the yield of tar was 0.41%.

[0107] In Example 32, the mass ratio of catalyst to bamboo waste was 30%; when the amount of bamboo powder used was 5.0 g, the amount of catalyst used was 1.50 g. The resulting bamboo vinegar solution had a pH of 2.71 and a density of 1.007 g / cm³. 3 The relative content of organic acids was 38.8%, the yield of bamboo vinegar was 31.8%, and the yield of tar was 0.27%.

[0108] Table 6. Application effects under different catalyst-to-material mass ratios

[0109]

[0110] As shown in Table 6, with Cu 0.1 Mn1O x Increasing the catalyst dosage reduced the tar yield from 3.69% to 0.27%, while increasing the relative organic acid content from 28.8% to 38.8%. Specifically, when the catalyst-to-bamboo waste mass ratio was 10%, the tar yield decreased to 1.31%, and the relative organic acid content increased to 36.8%, achieving significant tar removal and organic acid enrichment even with a relatively low catalyst dosage. Further increasing the catalyst-to-bamboo waste mass ratio to 20%-30% resulted in a further decrease in tar yield, but the catalyst dosage increased significantly, and the bamboo vinegar yield did not improve significantly. Considering catalyst dosage, bamboo vinegar yield, tar removal effect, and engineering application cost, the optimal catalyst-to-bamboo waste mass ratio is 10%.

[0111] Example 33 Effect of reaction time on the yield of bamboo vinegar and tar under photo-driven thermocatalysis

[0112] This set of examples illustrates the effect of reaction time on the yield of bamboo vinegar and tar under preferred light intensity. 5.0 g of dry bamboo powder and 0.50 g of Cu prepared in Example 1 were used. 0.1 Mn1O x The catalyst was loaded into a quartz tube, which was then placed inside a photothermal tube reactor with a light intensity of 1.2 kW·m. -2 The air flow rate was 40 mL / min, and the reaction time was controlled at 5 min, 10 min, 15 min, 20 min, 25 min, 35 min, 50 min and 60 min respectively, while keeping other conditions the same.

[0113] like Figure 7 As shown, when the reaction time was 5 min, 10 min, 15 min, 20 min, 25 min, 35 min, 50 min and 60 min, the yield of bamboo vinegar was 0.4%, 14.2%, 19.8%, 33.2%, 35.4%, 38.2%, 37.8% and 37.4%, respectively, and the yield of tar was 0, 0.34%, 0.42%, 1.30%, 1.31%, 1.42%, 1.18% and 1.32%, respectively. In the initial stage of the reaction, the rapid pyrolysis of the raw materials caused a small, instantaneous accumulation of tar, leading to a rapid increase in the yield of bamboo vinegar. As the reaction progressed, the Cu-Mn redox cycle stably regenerated active oxygen, maintaining a low tar content level. The yield of bamboo vinegar gradually approached its peak of 38.2%. Throughout the 60-minute process, no deactivation phenomena such as large-scale tar accumulation or a sharp drop in product yield were observed, confirming that the catalyst possesses both excellent tar removal capabilities and operational stability. It is suitable for the continuous pyrolysis process of bamboo waste to prepare low-tar bamboo vinegar, exhibiting outstanding overall photothermal synergistic catalytic effect. High-quality bamboo vinegar can be obtained without complex post-treatment, demonstrating promising prospects for industrial application.

Claims

1. A method for preparing a copper-manganese composite oxide catalyst, characterized in that, Includes the following steps: a. Dissolve citric acid, copper nitrate, and manganese nitrate in deionized water and stir until homogeneous to form a mixed solution; b. Add nitric acid and ethylenediamine to the mixed solution obtained in step a, continue stirring, and then add ammonia dropwise to adjust the pH to 6-7; c. Heat and stir the solution obtained in step b until a gel-like sample is formed; dry and age the gel-like sample to obtain the catalyst precursor. d. Calcine the catalyst precursor obtained in step c under an inert atmosphere; e. The sample obtained in step d is calcined in air and then cooled to obtain a copper-manganese composite oxide catalyst.

2. The preparation method of the copper-manganese composite oxide catalyst according to claim 1, characterized in that, Step d specifically involves: transferring the catalyst precursor obtained in step c into a quartz tube, introducing an inert atmosphere to remove air, then heating it to 400°C at a heating rate of 10°C / min, calcining it for 4 hours, and then allowing it to cool naturally after calcination.

3. The preparation method of the copper-manganese composite oxide catalyst according to claim 1, characterized in that, Step e specifically involves transferring the sample obtained in step d into a muffle furnace, heating it to 400°C at a heating rate of 10°C / min in an air atmosphere, holding it at that temperature for 4 hours, and then allowing it to cool naturally.

4. The preparation method of the copper-manganese composite oxide catalyst according to claim 1, characterized in that, The drying and aging conditions in step c are: drying and aging at 80℃ for 24 hours.

5. The copper-manganese composite oxide catalyst prepared by the method according to any one of claims 1 to 4.

6. The copper-manganese composite oxide catalyst according to claim 5, characterized in that, The molar ratio of Cu to Mn in the copper-manganese composite oxide catalyst is 0.1:1-0.5:

1.

7. The copper-manganese composite oxide catalyst according to claim 6, characterized in that, The molar ratio of Cu to Mn in the copper-manganese composite oxide catalyst is 0.1:

1.

8. The application of the copper-manganese composite oxide catalyst according to any one of claims 5-7 in the preparation of low-tar bamboo vinegar by photo-driven pyrolysis of bamboo waste.

9. The application according to claim 8, characterized in that, The photo-driven pyrolysis is carried out in a photothermal tube reactor. The bamboo waste and the copper-manganese composite oxide catalyst are loaded into a quartz tube, and then the quartz tube is placed in the photothermal tube reactor to carry out the photo-driven pyrolysis catalytic reaction; the reaction atmosphere is air.

10. The application according to claim 9, characterized in that, The air flow rate is 20-60 mL / min; the light intensity is 0.4-1.8 kW·m. -2 The mass ratio of catalyst to bamboo waste is 3%-30%.